Glottodydaktyka i językoznawstwo – razem czy osobno? - Śliwa, Dorota (Neofilolog, 2010)
The article concerns the relation between linguistics and glottodidactics. In the first part, we present a synthesis of problems found when these two disciplines confront each other. The reply to the question about the identity of linguistics is the concept of a sign as a cluster of relations (cognitive, pragmatic, communicative, etc.) developed by Krąpiec in the sense proposed by Aristotle and St. Thomas Aquinas. Key also is the concept of a subjective and predicative structure as a tool to describe the conceptual structure. The cluster of relations mentioned before undergoes syntactic transformations in the text. This proposition considers both cognitive and communicative functions of a language and takes a positive stance on the experiences of foreign language didactics.